Modernistyczna obsceniczność w przekładzie: ukraińskie i rosyjskie tłumaczenia Kochanka Lady Chatterley D.H. Lawrence’a u schyłku ZSRR - Saweneć, Andrij (Przekłady Literatur Słowiańskich, 2021)
<p lang="pl-PL" style="margin-bottom: 0cm; background: transparent; border: none; padding: 0cm; font-style: normal; font-weight: normal; line-height: 150%; page-break-inside: auto; widows: 2; orphans: 2; text-decoration: none; page-break-before: auto; page-break-after: auto;" align="JUSTIFY">The paper focuses on Ukrainian and Russian translations of Lady Chatterley’s Lover by D. H. Lawrence, published in 1989 and 1990. The framework for the analysis is provided by Loren Glass’s idea of a significant role of obscene vocabulary in the aesthetics of the twentieth-century Anglo-American literary modernism. The comparison of the two translations shows significant differences in the translators’ approaches to rendering Lawrence’s sexual-based language.